Miskonsepsi adalah perbedaan antara konsep yang dipahami dengan penjelasan para ahli. Penelitian ini bertujuan untuk menganalisis kembali miskonsepsi pada buku teks Biologi SMA kelas XI. Penelitian ini menggunakan metode meta analisis. Meta Analisis merup - Latifa Vita Vela (Universitas Nusantara PGRI Kediri, 2021)
Learning media is part of learning resources which is a combination of software (teaching materials) with hardware (learning tools. One type of learning media is e-learning. E-learning is a learning medium that uses the internet to deliver learning materials from teachers to students. One of the e-learning media is edmodo. Edmodo is a learning platform intended for students, teachers and parents. The purpose of this study was to determine the benefits of using edmodo in the learning process of biology. This type of research is a meta-analysis. Meta analysis is collecting and analyzing data from research results from relevant journals. The data were obtained by studying the literature on the articles on Google Scholar using the keywords